Occurrence of Contralateral Lymph Neck Node Metastasis in Patients with Squamous Cell Carcinoma of the Oral Cavity - Donaduzzi, Liziane C. (Medicina Oral S.L., 2014)
Introduction: Squamous cell carcinoma represents about 90% of malignancies of the mouth and about 38% of the head and neck tumors. The behavior of the cancer is very aggressive, presenting early cervical metastasis and, often contralateral ranging from 0.9 to 36%. Objectives: This study aims to analyze clinical and pathological factors that may influence metastasis of squamous cell carcinoma in cervical lymph nodes and relate this occurrence in the contralateral primary tumor, with disease prognosis and the interference of this type of metastasis in the survival rate of patients with this pathology. Material and Metohds: It was conducted a retrospective study from medical records of patients with Squamous Cell Carcinomas with homolateral lymph node metastasis and contralateral attended at the clinic of Head and neck surgery of Hospital São Vicente de Paulo in Passo Fundo – RS - Brazil, from 2000 to 2008. Results: Analyzing the charts of patients with metastatic and metastatic contralateral side it was observed that patients with initial stage presented a higher survival with statistical significance (p=0,035). Conclusions: The occurrence of metastases in lymph nodes of contralateral position to the primary lesion was not the main fator that influenced the survival of the group. Key words:Squamous cell carcinoma, oral cavity, contralateral, death rate, lymphatic metastasis, prognosis.